Study on the spatial spillover effect of reclaimed water utilization efficiency in water environment-sensitive areas with heterogeneous technology - Wei Jin; Shuhan Gao; Wei Jiang; Huimin Wang (Water Resources and Industry)
As a key path to alleviate the double pressure of economic and social development and ecological environment protection in water-sensitive areas, reclaimed water is of great significance to coordinately promote carbon reduction, pollution reduction, green expansion and growth. This paper uses the three-stage Slack-Based Measure (SBM) model to measure the efficiency of recycled water utilization in 41 cities in the Yangtze River Delta, and based on the characteristics of technological heterogeneity, systematically exploring the spatial correlation mechanism of recycled water utilization. The results show that: firstly, after excluding external environmental factors and random factors, the utilization efficiency of reclaimed water in different cities decreased significantly compared with before improvement. The utilization efficiency of recycled water in each city has dropped significantly compared with that before excluding external environmental factors and random factors. Secondly, government policy incentive is the key factor to improve the efficiency of reclaimed water utilization, and the leading role of science and technology innovation is limited to the cluster frontier in the low innovation level area. Thirdly, from the perspective of spatial spillover effect, the resident population significantly improved the efficiency of reclaimed water utilization in the region while suppressing the efficiency value of surrounding areas; the construction of water supply and drainage infrastructure inhibits the efficiency of reclaimed water utilization in all regions. Therefore, local governments should guide the use of reclaimed water through policy formulation and attach importance to technological innovation oriented by environmental protection. Optimize the construction of reclaimed water infrastructure based on the relationship between supply and demand, and improve the efficiency of reclaimed water utilization, so as to achieve the harmonious development of man and nature.